Kalender Buddhis Berbasis Android - ., Kustadi; Tandoyo, Cynthia Dewi; Kurniawan, Didik (Jurnal Komputasi, 2017)
There are six religions in Indonesia, one of them is Buddha. Every religions have their own religious days, including Buddha. To see the religious days, a Buddhist uses the combination of both Solar Calendar and  Lunisolar/Chinese Calendar. There are not many people can memorize all religious days. They will save the file contain the list of religious days in computer, flash disk or a printout file. In this research, the researcher will develop an android  calendar application that not only can convert Chinese Calendar into Solar Calendar, but also show the religious days on that day, and the religious days in a year. In this application, SQLite database will be used to record all the religious days.